Maternity incentive scheme on safe delivery services in rural area of Kavre district - Baniya, A; Chhetri, D; Pokhrel, B (Journal of Chitwan Medical College, 2015)
Maternity incentive schemes were to encourage mothers to use skilled birth attendance for the best prevention of maternal and child death whereas the pregnant women should have access to high quality prenatal care which, they can afford and where, they are treated with respect. The objective of the study was to determine the knowledge and utilization of maternal incentives scheme on delivery services at rural area of Nepal. This study was cross-sectional descriptive in nature and Study was conducted in Panchkhal VDC, Kavre district of Nepal.The numbers of married women of reproductive age group were the study population. The sample size was taken as 96. Most of the respondent had primary education (38.5%) and illiterate (15.6%). Highest mobilization of sources which provided throughout the health institute disseminates the MIS information During the study seventy nine mothers went to hospital for treatment. Utilization of incentive helps to change the delivery behavior (practice) of women (78%) within the hospital services by the skilled birth attendants. The 54.2% were not getting money (private hospital) for delivery and 13.5% respondents used money in nutrition and transport, 11.5% used in medicine and 1.0% respondent didn’t spend money. Low income and poor women (63%) have been more benefited from the incentive scheme followed by Janajati (12.5%), Dalit (12.5%) and rural women (9.4%) respectively. Importance of maternity incentive scheme (MIS) on safe delivery services (SDS) needs to be disseminated in rural community through integrated health education program. Most of the respondents reported that only incentive is not the matter of utilization of hospital services, but the issue of mother and child health.